Prevalence of multidrug-resistant Acinetobacter baumannii in intensive care unit admitted patients from a hospital in Dhaka City, Bangladesh - Mannan Sharif, Maliha Abdul; Tabassum, Nabila; Faruque, Md. Omar (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.